Multiomics Approach to Novel Therapeutic Targets for Cancer and Aging-Related Diseases: Role of Sld7 in Yeast Aging Network - ARĞA, KAZIM YALÇIN (MARY ANN LIEBERT, INC, 2017)
Genome instability has long been implicated as a salient causal factor in aging and age-related diseases such as cancer and neurodegeneration. However, the molecular mechanisms associated with genome instability remain unclear. Recent studies suggest growth signaling in the organism Saccharomyces cerevisiae and in higher eukaryotes might affect oxidative stress and aging/age-related diseases by activating DNA replication stress that causes DNA damage. In this broader integrative biology and clinical context, MDM two binding protein (MTBP) is a binding protein that has a role in activation of the tumor suppressor protein p53. Clinical studies suggest that the increase in expression of MTBP leads to reduction in survival of breast cancer patients. The functional homolog of MTBP in yeast, Sld7, is a hitherto uncharacterized protein that decreases the affinity of Sld3 (Treslin/Ticrr in humans) toward Cdc45 in the cell cycle process of S. cerevisiae. To investigate the putative function of Sld7 in chronological aging and replicative life span, we applied a network biology approach, integrating interactome and transcriptome data of budding yeast. The cell cycle and chronological aging networks of proteins in budding yeast were reconstructed. Furthermore, through meta-analysis of cell cycle and chronological aging-associated transcriptome datasets, we constructed coexpression networks and identified coexpressed gene clusters. In this study, we propose a dual role for Sld7: it participates in macromolecular complex binding in the cell cycle and has oxidoreductase activity in chronological aging in budding yeast. These potential roles of Sld7 in yeast can offer new insights on the role of MTBP in humans and consequently might lead to novel strategies for treatment of cancers and aging-related diseases.
Keywords: biomarkers; cancer; diagnostic medicine; drug research and OMICS; interactome; CHROMOSOMAL DNA-REPLICATION; SACCHAROMYCES-CEREVISIAE; PROTEIN LOCALIZATION; GENOME INSTABILITY; GLOBAL ANALYSIS; MESSENGER-RNA; LIFE-SPAN; INITIATION; EXPRESSION; GROWTH